Pengaruh kepemimpinan terhadap kinerja pustakawan di perpustakaan - Anwar Syamsuddin (Al Maktabah, 2007)
On the basis of the research conducted by the writter, this article is aimed to find out the impact of leadership styles on the librarian performance at the UIN Syarif Hidayatullah main library. There are three important issues of leadership styles discussed in this article, namely directive style, participative style and supportive style. By using the anova tables, there are no any indications that both the directive and supportive styles have implication on the librarian performance, but in term of the participative style the writter, obviously, found out that this style has implication on librarian performance at the UIN Syarif Hidayatullah main library. Key Words: Leadership styles, library performance.